Shear-wave elastography for breast masses: local shear wave speed (m/sec) versus Young modulus (kPa) - Ji Hyun Youk; Eun Ju Son; Ah Young Park; Jeong-Ah Kim (Ultrasonography, 2014)
Purpose: To evaluate and compare the performance of shear-wave elastography (SWE) for breast masses using the local shear wave speed (m/sec) vs. Young modulus (kPa). Methods: A total of 130 breast lesions in 123 women who underwent SWE before ultrasound- guided core needle biopsy or surgical excision were included. With the region-of-interest placed over the stiffest areas of the lesion on SWE, the quantitative mean, maximum, and standard deviation (SD) of the elasticity values were measured in kPa and m/sec for each lesion. The SD was also measured with the region-of-interest including the whole breast lesion (wSD). The area under the receiver operating characteristic curve (AUC), sensitivity, and specificity of each elasticity value measured in kPa and m/sec were compared. Results: Of the 130 lesions, 49 (37.7%) were malignant and 81 (62.3%) were benign. The AUCs for the mean, maximum, and SD of the elasticity values using kPa and m/sec did not differ significantly: mean, 0.974 vs. 0.974; maximum, 0.960 vs. 0.976; SD, 0.916 vs. 0.916. However, the AUC for wSD showed a significant difference: 0.964 (kPa) vs. 0.960 (m/sec) (P=0.036). There was no significant difference in the sensitivity and specificity of the mean, maximum, and wSD of the elasticity values. However, the specificity of the SD was significantly different between the two different measurements: 95.1% (kPa) vs. 87.7% (m/sec) (P=0.031). Conclusion: The quantitative elasticity values measured in kPa and m/sec on SWE showed good diagnostic performance. The specificity of the SD and AUC of the wSD measured in kPa were significantly higher than those measured in m/sec.